Obstetric outcome study of oligohydramnios beyond 34 completed weeks of gestation - K. R., Hema; H. S., Lalitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Perinatal morbidity and mortality are significantly increased when oligohydramnios is present. As the amniotic fluid volume decreases, the perinatal mortality rate increases. The incidence of major congenital anomalies with IUGR also increases as the amniotic fluid volume declines. There is a close association between declining placental function in the latter part of the third trimester and amniotic fluid volume1. Thus, post term patients are at a greater risk for development of oligohydramnios. Fetal anomalies that results in oligohydramnios classically involve the urinary tract. The most frequently mentioned renal anomalies include bilateral renal agenesis, multicystic dysplastic kidneys, bladder outlet obstruction and infantile polycystic kidneys. Methods: All antenatal patients seen in the Department of Obstetrics and Gynecology at Sri Siddhartha Medical College and Research Centre between January 2015 to January 2017, who were willing to participate in the trial study were enrolled. Ultrasound GE Voulson S8-PRO equipped with 3.5 MHz transducer was used to measure the amniotic fluid index. The AFI in each group was noted and the pregnancy outcome in each group was determined. At the time of delivery following data variables were collected and compiled. Results: There were 105 women, who were divided into three groups of 35 each. Those women with AFI<5 had more chances of emergency caesarian section, the causes were fetal distress with variable and late fetal heart decelerations. The incidence of meconium stained liquor and NICU admission were more. Conclusions: The women with AFI<5 had more chances of emergency caesarian section, the causes were fetal distress with variable and late fetal heart decelerations. Amniotic Fluid Index is a valuable screening test for detecting fetuses that may have poor perinatal outcome.